A modelagem matemática na merenda escolar nos anos finais do ensino fundamental - Grimaldi, Fernando Carvalho (2015)
This study aims to present the teaching of mathematics in an alternative perspective, in which the mathematical knowledge arises from the need to solve real problems, with the possibility of a critical approach to certain issues of the students` interests. Thus, this research will investigate the potential of Mathematical Modeling, making it happen. In view of this argument, we intend to answer the following question: is the dynamics of Mathematical Modeling an incentive for the learning of mathematics? Teaching using the Mathematical Modeling requires choosing a theme as a starting point and the search will turn around the School Meals. As a theoretical framework used to develop the study, quoted works on Mathematical Modeling and as a research methodology, the choice was the Didactic Engineering. The research focused students from the ninth grade of two public schools, one in Rio de Janeiro city and the other in Duque de Caxias, totaling seventy students. We believe that mathematical modeling will make the students realize the importance of mathematics and hence their interests in learning it will be higher. We end this survey with the drawing up of an Educational Product, in the form of an educational proposal in view of publication, as a teacher book.